Indonesia-ASEAN Institutional Roles and Challenges in the Crisis of the Liberal Order - Pradana, Reza Ardiansyah; Darmawan, Wawan Budi (Intermestic: Journal of International Studies, 2023)
The clash of interest and influence between the United States and China after the Cold War in the Asian region has contributed to the increasing number of threat perceptions in Southeast Asia and ASEAN institutions. The deepening crisis of the liberal international order through the leadership of the United States has proven to have decreased its influence due to internal rather than external behavior during the Donald Trump era. Indonesia-ASEAN has always tried to build a complex institutional role with the status attached to it. This study shows that ASEAN's institutional complexity is successful through the great powers’ rivalry management between the United States and China. Indonesia-ASEAN has become a subject rather than an international object in facing discursive challenges through historical roots, the spirit of Indonesia-ASEAN foreign policy, norms, and decision-making processes. By using the system dynamics method, it will be seen how complex the influence of the liberal international order is by comparing perceptions between other regions and the security cooperation that has been formed to balance China's influence, and explains the role of Indonesia-ASEAN in responding to times that are considered a crisis. The conclusion of this study lies in how great power pressure on ASEAN will have a worse and more dangerous impact so that Indonesia-ASEAN through the value of solidarity has succeeded in managing the rivalry of great powers and being soft on perceived threats during the liberal international order crisis.